Polymorphism in the Vesicular Monoamine Transporter 2 Gene Decreases the Risk of Parkinson’s Disease in Han Chinese Men - Xinglong Yang; Pingrong Xu; Quanzhen Zhao; Ran An; Hua Jia; Zhuolin Liu; Yanming Xu (Parkinson's Disease)
Background. Polymorphisms rs363371 and rs363324 in the vesicular monoamine transporter 2 (VMAT2) gene have been associated with risk of PD in an Italian population, and our aim is to investigate the association between the two single-nucleotide polymorphisms and PD in Han Chinese. Methods. 561 Han Chinese PD patients and 491 healthy age- and gender-matched controls were genotyped using Ligase detection reaction (LDR) method. Result. Both of patient and control groups showed similar genotype frequencies between patients and controls at both rs363371 and rs363324, as well as similar minor A allele frequencies at rs363371 (P=0.452) and rs363324 (P=0.413). None of the observed haplotypes showed a significant association with PD. Subgroup analysis by gender and age at onset revealed a significant association between the A allele of rs363371 and PD in Han Chinese males relative to healthy controls (OR 0.799, 95%  CI 0.665 to 0.959, P=0.016), and this association remained significant after adjusting for age (OR 0.785, 95%  CI 0.652 to 0.945, P=0.011). Conclusion. These results suggest that polymorphism of VMAT2 locus is associated with risk of PD in Han Chinese overall but that the A allele at rs363371 may protect against PD in Han Chinese males.